Elucidating the molecular bases of epigenetic inheritance in non-model invertebrates: the case of the root-knot nematode Meloidogyne incognita - Perfus-Barbeoch, Laetitia; Castagnone-Sereno, Philippe; Reichelt, Michael; Fneich, Sara; Roquis, David; Pratx, Loris; Cosseau, Céline; Grunau, Christoph; Abad, Pierre (Frontiers in Physiology, 2014)
Root-knot nematodes of the genus Meloidogyne are biotrophic plant parasites that exhibit different reproduction modes, ranging from classical amphimixis to obligatory mitotic parthenogenesis (apomixis), depending on the species. Meloidogyne incognita, an apomictic species, exhibits a worldwide distribution and a wide host range affecting more than 3,000 plant species. Furthermore, evidences suggest that apomixis does not prevent M. incognita from adapting to its environment in contrast to what is expected from mitotic parthenogenesis that should theoretically produce clonal progenies. This raises questions about mechanisms of genome plasticity leading to genetic variation and adaptive evolution in apomictic animals. We reasoned that epigenetic mechanisms might in part be responsible for the generation of phenotypic variants that provide potential for rapid adaptation. We investigated therefore the principal carriers of epigenetic information, DNA methylation and post-translational histone modifications. Even if M. incognita possesses the epigenetic machinery i.e. chromatin modifying enzymes, 5-methyl-cytosine and 5-hydroxy-methyl-cytosine content is absent or very weak. In contrast, we demonstrated that the canonical histone modifications are present and chromatin shows typical nucleosome structure. This work is the first characterization of carriers of epigenetic information in M. incognita and constitutes a preamble to further investigate whether M. incognita development and its adaptation to plant hosts are under epigenetic control.